54.8k views
5 votes
Let g(x)=2x and h(x)=x2+4. Find the value. (hog) (0)

User Randall
by
5.1k points

1 Answer

4 votes

Answer:

4

Explanation:

It's much easier to see the meaning if brackets are used.

h(g(x) ) = h·g(x)

What this means is that in h(x) where ever there is an x, put a g(x)

h(x) = x^2 + 4

h(g(x)) = [g(x)]^2 + 4

Now where ever you see a g(x), put 2x

h(g(x))= (2x)^2 + 4

h(g(x)) = 4x^2 + 4

Now solve for h(g(0)) which means where ever you see a x substitute a 0.

h(g(0)) = 4*(0) + 4

h(g(0)) = 4

User Jemz
by
5.0k points